Leveraging communities of practice to cultivate entrepreneurial mindset - Sedlan Kőnig, Ljerka (Naše gospodarstvo, 2024)
This paper explores the role of Communities of Practice (CoPs) as a potential teaching tool to better promote an entrepreneurial mindset, particularly in the context of higher education. Through a systematic review of existing learning theories and the concept of CoPs, this paper identifies the challenges of entrepreneurial education and proposes changes in higher education that focus on creating entrepreneurial awareness, enhancing entrepreneurial competencies and developing students' entrepreneurial identity to foster an entrepreneurial mindset by supporting formal higher education with informal educational practices such as CoPs. The originality of this paper lies in the presentation of the alternative concept of Accountable Entrepreneurial Education. By combining theoretical insights with practical examples, this paper serves as a valuable resource for educators, researchers and practitioners in the field of entrepreneurship education.
Keywords: entrepreneurial behaviour; higher education; inovativno mišljenje; podjetniško vedenje; podjetništvo; teaching tool; učni pripomočki; visokošolsko izobraževanje